Medication Adherence Among Outpatients with Hypertension at Minh Tri Health Point, Kim Anh Commune Health Station, Hanoi, Vietnam, 2025 - Phuong Lan, Luong Thi; Huong, Tran My; Ngoc Nghia, Nguyen; Thi Thu Hang, Nguyen; Lan Ngoc, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Background: Medication adherence plays a crucial role in achieving optimal blood pressure control and preventing complications among outpatients with hypertension. Objectives: To assess the level of medication adherence and to identify factors associated with medication adherence among hypertensive outpatients. Methods: A cross-sectional study was conducted among 213 hypertensive outpatients at Minh Tri Health Point, Kim Anh Commune Health Station, Hanoi, Vietnam, in 2025. Medication adherence was assessed using the 9-item Hill-Bone Medication Adherence Subscale. Data were collected through face-to-face interviews and analyzed using descriptive statistics and bivariate analysis. Results: Only 30.5% of outpatients demonstrated good medication adherence. Factors significantly associated with medication adherence included occupation, monthly income, duration of hypertension diagnosis, number of antihypertensive medications used (p < 0.05). Conclusions: Medication adherence among hypertensive outpatients was low. Some demographic characteristics and medical history have a significant association with medication adherence in the treatment of hypertension. So, strengthening health education and patient-centered interventions at the primary care level is essential to improve adherence and enhance hypertension control outcomes.